2017
DOI: 10.1371/journal.pone.0170760
|View full text |Cite
|
Sign up to set email alerts
|

Lhx8 interacts with a novel germ cell-specific nuclear factor containing an Nbl1 domain in rainbow trout (Oncorhynchus mykiss)

Abstract: Lhx8 is an important transcription factor that is preferentially expressed in germ cells. Lhx8 null mice are infertile due to lack of oocytes and impairment of the transition from primordial follicles to primary follicles. Lhx8 deficiency also affects the expression of many important oocyte-specific genes. In this study, we report the characterization of rainbow trout lhx8 genes and identification of a novel germ cell-specific nuclear factor that interacts with Lhx8. Two lhx8 genes, lhx8a and lhx8b, were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…As obesity led to an increase in the number of atretic follicles, we wondered if this increase was induced by the abnormal expressions of the genes BMP4, GDF9, or LHX8 that play key roles during ovarian follicular development (Fu et al, 2017;Liu et al, 2017;Stocker et al, 2020). Our results demonstrated that there were no significant differences in their mRNA expression levels among the three mice groups, suggesting that the increased number of atretic follicles was not caused by abnormal BMP, GDF9, and LHX8 gene expression.…”
Section: Discussionmentioning
confidence: 71%
“…As obesity led to an increase in the number of atretic follicles, we wondered if this increase was induced by the abnormal expressions of the genes BMP4, GDF9, or LHX8 that play key roles during ovarian follicular development (Fu et al, 2017;Liu et al, 2017;Stocker et al, 2020). Our results demonstrated that there were no significant differences in their mRNA expression levels among the three mice groups, suggesting that the increased number of atretic follicles was not caused by abnormal BMP, GDF9, and LHX8 gene expression.…”
Section: Discussionmentioning
confidence: 71%
“…figla plays a key role in the early ovarian differentiation of zebrafish. In addition, the interaction between lhx8 and figla regulates the growth and differentiation of mouse oocytes [ 47 ]. In zebrafish with bmp15 knockout, gonads are normally developed at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…Studies about paralogues of borealin proteins are very scarce. The expression distribution of Cdca9, the only known paralogue of borealin proteins, also known as Borealin‐2 and Dasra A, was once investigated in Oncorhynchus mykiss (Fu et al ., 2017). The paralogue is still shrouded in mystery.…”
Section: Figurementioning
confidence: 99%
“…The sequence and phylogenetic analysis suggested that Cdca9 was highly conserved in fish, sharing the highest level of identity with Triplophysa tibetana (80.31%), and was more similar to T. tibetana than other species in the resulting tree (Supporting Information Figure S1). Similar to borealin in vertebrates, loach Cdca9 had an Nbl1 domain which resembled in O. mykiss (Fu et al ., 2017). This domain encodes a protein that belongs to the Nbl1_Borealin_N family, containing both the N terminal region of borealin and Nbl1 (El‐Gebali et al ., 2019).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation